Kerjasama Kegiatan Kemahasiswaan BK2PTKI – Badan Koordinasi Kemahasiswaan Perguruan Tinggi Kristen Indonesia - Libianko Sianturi; Sindak Hutauruk; Rimbun C.D. Sidabutar; Jamser Simanjuntak (LPPM Universitas HKBP Nommensen, 2022)
The purpose of this community service activity is to provide an overview, understanding and alternative forms of student collaboration that can be carried out together in the BK2PTKI – Badan Koordinasi Kemahasiswaan Perguruan Tinggi Kristen Indonesia - Indonesian Christian Higher Education Student Cooperation Agency. At the national meeting with the theme: revitalization of the student body in the era of the kampus merdeka and the sub-theme: strategy for managing student activities in the era of the kampus merdeka, the Presenter Team was given the opportunity to deliver material with the topic: